Exploring the Nexus between Service Quality and Student Satisfaction and Loyalty in Ghana’s Upper East Region: Insights from Undergraduate Students at Regentropfen University College - , Suglo Kabinaa Enoch; , Stanley Appiah Essuman; , Richard Fiifi Agyakwa; , Dacosta Aboagye; , Ebenezer Agudey Akuteye (Archives of Current Research International, 2025)
The purpose of this study was to explore undergraduate students’ expectations and satisfaction levels with customer service quality. This study employed the Expectancy Confirmation Theory (ECT) and a descriptive design with a sample of 385 undergraduate students selected from a population of 635 using a simple random sampling technique. Data were collected using a closed-ended questionnaire. The instrument was piloted using a 30% of the potential respondents which produced a Cronbach's alpha reliability coefficient of .862 demonstrating that the constructs of the questionnaire were highly internally consistent. Descriptive and inferential analysis tools were used. The results revealed that the students generally held high expectations for the institution (M=2.66-3.74). Again, a statistically significant difference between satisfaction levels students expectations was found F(385)= 9.228, (p<.001). The study concluded that RUC successfully fulfills students' core academic and community expectations, with most students indicating that they would choose RUC again and support its mission. The students’ willingness to recommend RUC and participate in fundraising efforts suggests a strong foundation of loyalty. The study recommended maintaining high standards in friendliness, accessibility, and effective communication to sustain students’ satisfaction. Additionally, feedback channels could help identify specific areas within customer service where students feel underserved, enabling continuous improvement and student-centered growth at RUC.